Afrontamiento y apoyo familiar en personas con discapacidad visual adquirida, usuarios del centro tiflocultural municipal de Loja, periodo abril 2020 – febrero 2021 - Arévalo Carrera, Tatiana Paola (2021)
Acquiring a visual disability is more frequent due to multiple reasons and the process of adaptation to this new condition is an important matter for people with acquired visual disabilities, and their family environment; that is why this research work aims to solve the lack of studies on coping and family support for this population. The objective of this thesis is to identify how coping and family support affect the development and rehabilitation of people with acquired visual disabilities users of the ‘Centro Tiflocultural Municipal de Loja’ (Municipal Typhlo-cultural Center of Loja), time period April 2020 - February 2021. For this purpose, a descriptive research type was developed. In this research 10 users of the ‘Centro Tiflocultural Municipal de Loja’ participated, 2 women and 8 men. This research is based on specialized bibliographic sources on issues of visual disability, coping, and family support. The results obtained in this research show that people have inadequate coping when acquiring visual disability, leading to difficulties in their subsequent rehabilitation; at the same time, it was possible to show that the provided family support, the person who has acquired the disability, perceives it as appropriate, which allows them to cope with their new condition and rehabilitate.